2005
DOI: 10.1111/j.1365-2966.2005.09665.x
|View full text |Cite
|
Sign up to set email alerts
|

Stellar populations in a complete sample of local radio galaxies

Abstract: We investigate the nature of the continuum emission and stellar populations in the inner 1-3 kiloparsecs of a complete sample of twenty-four southern radio galaxies, and compare the results with a control sample of eighteen non-active early-type galaxies. Twelve of the radio galaxies are classified as Fanaroff-Riley type I (FRI), eight as FRII and four as intermediate or undefined type (FRx). Optical long-slit spectra are used to perform spectral synthesis as a function of distance from the nucleus at an avera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 22 publications
5
44
4
Order By: Relevance
“…There is increasing evidence that the host galaxies of various types of AGN are bluer than inactive ellipticals (Govoni et al 2000;Schade et al 2000;Örndahl et al 2003;Sanchez et al 2004;Jahnke et al 2004;Kotilainen & Falomo 2004;Hyvönen et al 2007a) and that they do not follow the color-magnitude relation of inactive Article published by EDP Sciences ellipticals (Peletier et al 1990) indicating a recent star formation episode. This scenario is also supported by optical spectroscopic studies of nearby radio galaxies (RG) (Raimann et al 2005;Holt et al 2007). The observed blue colors are not affected by the dust content of the galaxy, because in the presence of dust reddening the intrinsic color of the galaxy would be even bluer.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…There is increasing evidence that the host galaxies of various types of AGN are bluer than inactive ellipticals (Govoni et al 2000;Schade et al 2000;Örndahl et al 2003;Sanchez et al 2004;Jahnke et al 2004;Kotilainen & Falomo 2004;Hyvönen et al 2007a) and that they do not follow the color-magnitude relation of inactive Article published by EDP Sciences ellipticals (Peletier et al 1990) indicating a recent star formation episode. This scenario is also supported by optical spectroscopic studies of nearby radio galaxies (RG) (Raimann et al 2005;Holt et al 2007). The observed blue colors are not affected by the dust content of the galaxy, because in the presence of dust reddening the intrinsic color of the galaxy would be even bluer.…”
Section: Introductionmentioning
confidence: 65%
“…These studies have only recently been followed by systematic studies by e.g. Nolan et al (2001), Jahnke (2002), Raimann et al (2005) and Silva et al (2008). According to the unified model of radio-loud AGN, RGs are seen edge-on so that the bright central region is obscured, making spectroscopy of the inner part of the host galaxy much easier.…”
Section: Introductionmentioning
confidence: 99%
“…A set of 3CR and 6C sources at redshift ≈1 has been investigated with great detail in the nineties (Best et al 1997(Best et al , 1998(Best et al , 1999 to understand this effect (see also Inskip et al 2006a, and references therein). More recently the UV-excess has been found in local samples of radio galaxies as well (Aretxaga et al 2001;Raimann et al 2005).…”
Section: A Comparison Sample Of Large Size Radio Galaxiesmentioning
confidence: 97%
“…The presence of young stellar populations in these objects has been revealed several times (Holt 2009;Labiano et al 2008;deVries et al 2007;Tadhunter et al 2002). Their origin is attributed to the shocks generated by the young radio source expanding into the interstellar medium (Rees 1989;Mellema et al 2002;Bicknell et al 2000), and/or as the result of a galaxy merger process which, at some later epoch, also triggered the onset of the radio source (Raimann et al 2005;Holt 2009). …”
Section: Introductionmentioning
confidence: 94%
“…This is supported by existence of the dust lane in the optical counterpart (Ekers et al, 1978;Kotanyi & Ekers, 1979) in addition to a tenuous HI bridge reaching 400 kpc from the disk of NGC 612 towards its nearest neighbour, NGC 619 (Emonts et al, 2008). Furthermore, Tadhunter et al (1993) argue that recent star-formation has taken place, as suggested by the observation of strong and narrow absorption features in the optical spectrum, with weak [OII] and [OIII] emission and both Raimann et al (2005) and Holt et al (2007) observe a young stellar population throughout the stellar disk.…”
Section: Introductionmentioning
confidence: 88%